Best practices in forecasting labour demand in Europe : Report II - Arendt, Lukasz [Herausgeber]; Ulrichs, Magdalena [Herausgeber] (Instytut Pracy i Spraw Socjalnych, 2012)
This book describes systems of forecasting labour demand used in five Member States of the European Union (United Kingdom, Finland, Czech Republic, Germany, Netherlands). "The analysis of these systems, which may be seen as examples of the so called best practices, has led to the formulation of recommendations for the new Polish model and system of emplyment forecasting that is built within the EU co-funded project 'Analysis of the processes on the Polish labour market and in the area of social integration in the context of conducted economic policy', Task 2 'Establishing the integrated forecasting and information system providing employment forecasts'." (Hrsg., BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; Qualifikationsnachfrage; Qualifikationsbedarf; Prognose; Best practice; Bundesrepublik Deutschland; Finnland; Niederlande; Tschechische Republik; Vereinigtes Königreich